2019
DOI: 10.3390/ijms20102489
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening Guided Design, Synthesis and Bioactivity Study of Benzisoselenazolones (BISAs) on Inhibition of c-Met and Its Downstream Signalling Pathways

Abstract: c-Met is a transmembrane receptor tyrosine kinase and an important therapeutic target for anticancer drugs. In this study, we designed a small library containing 300 BISAs molecules that consisted of carbohydrates, amino acids, isothiourea, tetramethylthiourea, guanidine and heterocyclic groups and screened c-Met targeting compounds using docking and MM/GBSA. Guided by virtual screening, we synthesised a series of novel compounds and their activity on inhibition of the autophosphorylation of c-Met and its down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Accumulating evidences indicated that c-Met is canonically mediated by ERK1/2 pathway. 18 , 19 Therefore, we speculated that PHA-665752 inhibits the proliferation, migration and invasion of OS cells through the ERK1/2 pathway. To verify this conjecture, we performed Western blot analysis and found that the expression of pERK1/2 in OS cells was considerably upregulated when treated with PHA-665752, while the expression of ERK1/2 had no change ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidences indicated that c-Met is canonically mediated by ERK1/2 pathway. 18 , 19 Therefore, we speculated that PHA-665752 inhibits the proliferation, migration and invasion of OS cells through the ERK1/2 pathway. To verify this conjecture, we performed Western blot analysis and found that the expression of pERK1/2 in OS cells was considerably upregulated when treated with PHA-665752, while the expression of ERK1/2 had no change ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking, molecular dynamics, and virtual screening approaches can now be efficiently used for the design of new inhibitors of the MET kinase domain [27,56,[76][77][78][79][80]. From all these approaches, new potent compounds were obtained and more highlights revealed about MET kinase domain conformational behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of c-Met as a clinically significant oncogenic pathway, especially pertaining to resistance to chemotherapeutic drugs, has led to the investigation of several drugs aimed to target this specific downstream pathway. Zhang et al (2019) discussed the screening of multiple benzisoselenazolones (BISAs) in the inhibition of the c-Met signaling pathway. After rigorous screening and analysis of multiple BISAs, virtually all BISAs exhibited c-Met inhibitory and anti-tumor activity compared with Ebselen, a commonly known selenoorganic compound with antitumor and neuroprotective properties.…”
Section: Multi-modal-targeted Therapeutic Intervention Against Met Signalingmentioning
confidence: 99%
“…It was recommended that the isothiourea and heterocyclic groups be added to Ebselen to enhance its activity. Knowing that c-Met type II inhibitors have multiple targets, this class of drugs may have other inhibitory pathways, which have yet to be discovered ( Zhang et al, 2019 ).…”
Section: Multi-modal-targeted Therapeutic Intervention Against Met Signalingmentioning
confidence: 99%